Performance Audit on Medical Education Department in Jharkhand (2010-2015) - CAG of India (CAG of India)
Health care in the State faces acute shortage of doctors and para-medical personnel. To address this problem, initiatives taken by the Government to augment the medical institutions for producing trained medical personnel available for health services in the state prompted conduct of a performance audit on the Status of Medical Education System under the Allopath stream in Jharkhand covering the period of 2010-15. Some of the major audit findings are discussed below: 1. Establishment of three new Medical Colleges each in the Government Sector as well as under Public Private Partnership mode/private sector could not be achieved and even the meagre allotments of plan expenditure were surrendered which resulted in not achieving the annual target of 900 Under Graduate (UG) seats set by the Government in medical colleges in the State. 2. Not providing adequate funds in the budget resulted in not fulfilling the target of opening three paramedical courses as was envisaged in Annual Plan of 2011-12. So capacity augmentation of Para Medical Personnel for delivering better healthcare services could not be achieved. 3. Utilization of UG seats in Medical College was 1,279 against 1,390 sanctioned seats but in Post Graduate it was 708 against 959 sanctioned seats leaving 251 (26 per cent) vacant seats. This resulted in failure of the objective of State Government to increase the numbers of doctors/specialist doctors for induction into the health services. This could affect the provision of health services adversely in the State in the future. 4. In PMCH, Dhanbad admissions were made for additional seats during 2014-15 without approval of MCI due to which future prospects of students admitted to these additional seats remain uncertain. Further, PG courses in PMCH, Dhanbad could not be started due to acute shortage of faculty ranging between 53 per cent in 2010-11 to 60 per cent in 2014-15. The prospective students were denied the benefit of higher medical education. 5. Shortage of medical equipment in different departments of PMCH, Dhanbad ranged between 22 and 80 per cent. This could affect practical training of medical students and their education. 6. Medical equipment purchased using State plan and Centrally Sponsored Scheme fund worth ` three crore and ` 1.25 crore respectively were not put to use for want of reagents/technicians which led them being damaged or disused. 7. Due to shortage of faculty, actual teaching hours fell short of the prescribed minimum norms of MCI by 14 to 48 per cent in PMCH, Dhanbad which might have an adverse impact on quality of education. 8. Shortage of medical equipment ranged between 40 and 63 per cent in ANMTCs and GNMTC and was 72 per cent in the College of Nursing, Ranchi. Similarly, these were under staffed by 68, 72 and 89 per cent which might affect the quality of education imparted in the colleges. 9. Monitoring in PMCH, Dhanbad was deficient as only four meetings of the college council against the MCI requirement of 20 meetings were held during 2010-15. No inspection was done by higher authorities of the paramedical institutions. Inadequate monitoring may lead to shortage/irregularities being undetected and remedial measures not taken in time.
For the Period 2010-11 to 2014-15